نقد الأنثروبولوجيا اللغوية في القرن العشرين النسبيّة اللغوية وإرث ما بعد الحداثة - شباني, منذر; حمدان, ديمة محمد (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
تطرح الأنثروبولوجيا اللغوية عدة إشكاليات تتعلق بالنسق الذي يمكننا أن ندرس اللغة من خلاله لذا يبحث هذا المقال في المذاهب والأفكار والنظريات التي تناولت مسألة اللغة والظّاهرة اللغوية من حيث تكوّنها وتشكلها في نطاق الفكر الفلسفي, والعلمي , و إذا كان بإمكاننا أن نتوصل إلى نسق يحكم العلاقة اللغوية باستقلال عن الإنسان المتكلم , ونعرض أيضا وجهة نظر البنيوية والاتجاهات اللغوية الأخرى في القرن العشرين , ومناهجها , وصولاً إلى المنهج التاريخي الذي وقف في وجه هيمنة الفكر الإمبريالي, الفكر الذي حَجّم الظاهرة اللغوية مُغيّباً إياها عن المجتمع . The Linguistic Anthropology process many problematic thoughts , this problematic are all related with the arrangement which we can study language by its reveal.So, as we well see this essay is arguing in methods , ideas and theories which discuss the language matter and linguistic phenomenon as its formation in the philosophical and scientific field, and if we could get to an arrangement overrule the Linguistic relation as its independence of talking man , and we will try to expose the structuralism and other linguistic turns in the twentieth century ,and its methods , and the social historical order which had stand in the face of the dominance the imperialism thinking , which distort the linguistic phenomena and distance this phenomena of society .